In vivo survivality and optimization of parameters for biomass production of GDHA derivative of pasteurella multocida B:2 - Oslan, Siti Nur Hazwani (2013)
The gdhA derivative of Pasteurella multocida B:2 was earlier created, proven of their safety and was onsequently used to control haemorrhagic septicemia in cattle and buffaloes as a vaccine. However, the production cost of the vaccine is too high. This study highlights on low cost medium formulation to mass-produce the vaccine for field use.The survival period of the gdhA derivative Pasteurella multocida B:2 was studied. In the in vitro study, the effect of storage at different temperature revealed that the organism survived better when kept at 4oC compared to room temperature. In the in vivo study, the derivative strain attempted to release the kanamycin cassette after 8 h postintraperitoneal inoculation into mice, but none of the infected mice died. Successful reisolation of the derivative without cassette from the liver and lung of mice at 88 h postinjection indicated that the strain had significantly reduced the ability to spread and survive in vivo. However, following infection by the wild-type Pasteurella multocid B:2, all mice died in less than 24 hours. Subsequently, the wild type was successfully isolated from the heart, lung and liver of mice infected. Following successful in vitro and in vivo studies and the earlier studies that indicated the gdhA derivative Pasteurella multocida B:2 as a good potential for vaccine production.The effects of different nitrogen and carbon sources on biomass production and growth of mutant strain was subsequently studied. The yeast extract and glucose, as nitrogen and carbon source, respectively were proven to help in producing highest biomass. Using the shake-flask, the new growth medium was optimized and developed by Response Surface Methodology (RSM), and produced 3.1 mg/mL of biomass. The RSM suggested that 15.6 g/L of yeast extract, 1.9 g/L of glucose, 3.0 g/L of sodium chloride, and 2.5 g/L of sodium chloride were the optimum amount in the new growth medium to produce optimum product. Biomass production of the mutant strain was tested in a scaled-up 5 L bioreactor. A total volume of 3 L newly formulated medium was used at different oxygen levels. The highest biomass production was effectively at 50% dissolve oxygen, producing 3.50 mg/mL of the of dry cell weight. In conclusion,the improvement in productivity of the mutant gdhA derivative of Pasteurella multocida B:2 was increased 52.72% in shake-flask and 275.9% in bioreactor before nonoptimized medium through RSM method. The total cost of medium components developed in this study (RM7.61 per litre) was low compared with the commercial BHI medium (RM37.00 per litre), which is a reduction of 79%.